Strategi Integrasi Rantai Pasok Perikanan Nasional: Memperkuat Benteng Asia sebagai Pilar Ketahanan Ekspor Indonesia di Era Ketidakpastian Global - Mega Lenita Purnama (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study analyzes the strategic integration of Indonesia's fishery supply chain, positioning the Asian region as a cornerstone market to counter global economic volatility. Utilizing secondary data on fishery export values from 2019 to 2025, this research evaluates the trend of market shifts from traditional Western partners toward the more dynamic Asian corridor. The analysis reveals significant growth in South Asian markets, most notably in Bangladesh, which recorded an exponential increase in export value from USD 131.52 in 2019 to over USD 10,000 by 2024. These findings indicate that an Asia-centric supply chain integration effectively serves as an economic buffer against global market uncertainties. The study recommends strengthening bilateral trade diplomacy and enhancing product quality standardization to solidify Indonesia’s position as a leading provider of marine protein within the Asian region.